1996
DOI: 10.1016/0550-3213(96)00391-4
|View full text |Cite
|
Sign up to set email alerts
|

Near-BPS-saturated rotating electrically charged black holes as string states

Abstract: We construct generating solutions for general D-dimensional (4 ≤ D ≤ 9) rotating, electrically charged, black holes in the effective action of toroidally compactified heterotic (or Type IIA) string. The generating solution is parameterized by the ADM mass, two electric charges and D−1 2 angular momenta (as well as the asymptotic values of one toroidal modulus and the dilaton field). For D ≥ 6, those are generating solutions for general black holes in toroidally compactified heterotic (or type IIA) string. Sinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(134 citation statements)
references
References 17 publications
2
132
0
Order By: Relevance
“…In addition, it would be interesting to generalise these solutions to charged Kerr-de Sitter solutions in higher dimensions, thus extending the general spinning charged black holes with zero cosmological constant [16] and the general Kerr-de Sitter solutions, obtained recently in [17], to charged black holes in de Sitter backgrounds.…”
Section: Global Analysismentioning
confidence: 99%
“…In addition, it would be interesting to generalise these solutions to charged Kerr-de Sitter solutions in higher dimensions, thus extending the general spinning charged black holes with zero cosmological constant [16] and the general Kerr-de Sitter solutions, obtained recently in [17], to charged black holes in de Sitter backgrounds.…”
Section: Global Analysismentioning
confidence: 99%
“…We propose [184] an alternative way to circumvent the problems of the BPS electric black holes. Instead of defining the thermal entropy of the BPS black holes at the stretched horizon, we propose to calculate the thermal entropy of near extreme black holes at the event horizon.…”
Section: Near-extreme Black Holes As String Statesmentioning
confidence: 99%
“…We discuss rotating black holes in heterotic string on T 10−D (4 ≤ D ≤ 9) with general U (1) 36−2D electric charge configurations [184,449]. The generating solution is parameterized by the ADM mass M BH (or alternatively the non-extremality parameter m), […”
Section: Rotating Black Holes In Higher Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two main examples in the literature of generalised closed conformal Killing-Yano tensors that satisfy the anomaly equation. One is the generalized closed conformal Killing-Yano tensor, with torsion given by the 3-form flux H (Houri et al, 2010b), in Kerr-Sen black hole spacetimes in generic dimension: it satisfies the anomaly equation with f = 0 = ǫ (Chow, 2008;Cvetič and Youm, 1996;Sen, 1992). The other is minimal five-dimensional supergravity, with the torsion identified with the dual of Maxwell field T = * F/ √ 3, for the most general black hole solution (Chong et al, 2005a): in this case one has Perelomov (Olshanetsky and Perelomov, 1981) showed that the Toda chain can be obtained by projecting to lower dimension the geodesic equations on the Lie group X − = SO(n)\SL(n, R).…”
Section: Sp(n/4) Structuresmentioning
confidence: 99%